1975
DOI: 10.1111/j.1749-6632.1975.tb35999.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Electromagnetic Radiation on the Hematopoietic Stem Cells of Mice

Abstract: An increase in the leukocyte number in blood and a decrease in the total cell volume of the bone marrow and spleen were observed in mice after wholebody microwave irradiation (2450 MHz, lambda equals 12.5 cm, 100 mW/cm-2). The number of hematopoietic stem cells increased early after microwave irradiation (1626 plus or minus 53 CFU in bone marrow, 689 plus or minus 86 CFU in the spleen), as compared with that or control (598 plus or minus 92 and 349 plus or minus 79 CFU, respectively). Incorporation of 59Fe in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1980
1980
1998
1998

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…This is in contrast to a decrease in erythrocyte production in guinea pigs reported by . In the mice exposed by Rotkovska and Vacek (1975), the colonic temperature rose 2.3°C. Exposure to convectional heat sufficient to raise the colonic temperature 2.5°C produced reactions that were qualitatively, although not necessarily quantitatively, similar.…”
Section: An/mal Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to a decrease in erythrocyte production in guinea pigs reported by . In the mice exposed by Rotkovska and Vacek (1975), the colonic temperature rose 2.3°C. Exposure to convectional heat sufficient to raise the colonic temperature 2.5°C produced reactions that were qualitatively, although not necessarily quantitatively, similar.…”
Section: An/mal Experimentsmentioning
confidence: 99%
“…Increase in the number of hematopoietic endogenous colonies (ESC) in the spleens of X-irradiated mice after microwave exposure supports earlier observations of an elevation of the number of stern cells in the spleens of intact mice after microwave exposure alone (Rotkovska and Vacek, 1975). Results of both experiments indicate that microwaves may influence the intricate mechanisms that activate the pool of stern cells.…”
Section: An/mal Experimentsmentioning
confidence: 99%
“…The results of Czerski indicated that there was an increase in the number of anti-SRBC cells after six weeks 6-55 of irrad1at1on, but that after 12 weeks of irradiation, the effect had disappeae.i suggesting that the animals had accommodated physiologically to the radiation. Rotkovska and Vacek (1975) reported lymphocytosis following a brief, intense exposure to microwaves, and Pazclerova-Vejlupkova (1979) reiirted 1ymphopinia following chronic mi'rowave exposure at 24 niW/cm 2 . When…”
Section: Imt4ejnolocical Effectsmentioning
confidence: 99%